2019
DOI: 10.1242/jeb.201285
|View full text |Cite
|
Sign up to set email alerts
|

Upstroke-based acceleration and head stabilization are the norm for the wing-propelled swimming of alcid seabirds

Abstract: Alcids, a family of seabirds including murres, guillemots and puffins, exhibit the greatest mass-specific dive depths and durations of any birds or mammals. These impressive diving capabilities have motivated numerous studies on the biomechanics of alcid swimming and diving, with one objective being to compare stroke-acceleration patterns of swimming alcids with those of penguins, where upstroke and downstroke are used for horizontal acceleration. Studies of free-ranging, descending alcids have found that alci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
5
1
Order By: Relevance
“…During aquatic flight in extant penguins and volant auks, upstroke of the wings produces substantial forward thrust (propulsive force) (e.g., Clark and Bemis 1979 ; Johansson and Wetterholm Aldrin 2002 ; Watanuki et al 2006 ; Lapsansky and Tobalske 2019 ). This contrasts with aerial flight in birds, in which the generation of forward thrust is typically restricted to the downstroke phase ( Rayner 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…During aquatic flight in extant penguins and volant auks, upstroke of the wings produces substantial forward thrust (propulsive force) (e.g., Clark and Bemis 1979 ; Johansson and Wetterholm Aldrin 2002 ; Watanuki et al 2006 ; Lapsansky and Tobalske 2019 ). This contrasts with aerial flight in birds, in which the generation of forward thrust is typically restricted to the downstroke phase ( Rayner 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…During aquatic flight in extant penguins and volant auks, upstroke of the wings produces substantial forward thrust (propulsive force) (e.g., Clark and Bemis 1979;Johansson and Wetterholm Aldrin 2002;Watanuki et al 2006;Lapsansky and Tobalske 2019). This contrasts with aerial flight in birds, in which generation of forward thrust is typically restricted to the downstroke phase (Rayner 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Visual inspection of the aquatic data revealed pronounced head movement (relative to the body) in sync with the wingbeat cycle (i.e. body length varied with position in the stroke cycle) ( Lapsansky and Tobalske, 2019 ). Because of this, we smoothed the raw body-length data using the ‘smoothingspline’ method of fitting in MATLAB and a smoothing parameter of 1e-04 to account for the head movement of the bird.…”
Section: Methodsmentioning
confidence: 99%
“…Stroke-plane angle was calculated as the angle between the bird-centered position vector describing the path of the wrist between its minimum and maximum elevation relative to the direction the bird was traveling. For aquatic flights, used the position of the tail to calculate velocity, as our previous work has demonstrated that the head is an unreliable indicator of overall body motion in swimming alcids ( Lapsansky and Tobalske, 2019 ). Details of the velocity calculation, including how we corrected for the effects of pitching in our calculation, are described in more detail in Lapsansky and Tobalske, 2019 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation